2019
DOI: 10.1080/21691401.2019.1593858
|View full text |Cite
|
Sign up to set email alerts
|

Improved antibacterial function of Rifampicin-loaded solid lipid nanoparticles on Brucella abortus

Abstract: The objective of this study was to assess the antibacterial activity of Rifampicin-loaded solid lipid nanoparticles on Brucella abortus 544. Rifampicin-loaded solid lipid nanoparticles were prepared by a modified microemulsion/sonication method and characterized. The results showed the average size about 319.7 nm, PI about 0.20 and zeta potential about 18.4 mv, encapsulation efficacy and drugloading were equal to 95.78 and 34.2%, respectively, with a spherical shape. Drug release lasted for 5 days. The antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…The endothermic peak of RIF was shifted to a lower temperature in the physical mixture thermogram because the melting lipids tend to solubilize RIF. This result was previously observed by Ghaderkhani et al after the disappearance of the drug melting peak in the physical mixture thermogram of RIF and Stearic acid for SLNs preparation [23]. The thermogram of RIF loaded SLNs (F4) showed both endothermic and exothermic peak.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 84%
“…The endothermic peak of RIF was shifted to a lower temperature in the physical mixture thermogram because the melting lipids tend to solubilize RIF. This result was previously observed by Ghaderkhani et al after the disappearance of the drug melting peak in the physical mixture thermogram of RIF and Stearic acid for SLNs preparation [23]. The thermogram of RIF loaded SLNs (F4) showed both endothermic and exothermic peak.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 84%
“…• Promoting accumulation in target cells by means of active targeting (Maretti et al, 2017;Costa et al, 2018;Vieira et al, 2018;Hosseini et al, 2019;Banerjee et al, 2020). • Increasing inhibitory effect (i.e., decreasing MIC) over bacterial strains (Severino et al, 2015;Pignatello et al, 2017;Ghaderkhani et al, 2019;Rodenak-Kladniew et al, 2019).…”
Section: A Descriptive Analysis Of Therapeutic Application Fields Of Slnmentioning
confidence: 99%
“…The value of the zone of inhibition of OPL-SLNs against Pseudomonas aeruginosa and Staphylococcus aureus was observed 14.75±2.25 mm and 16.30±2.1 mm in 24 h respectively. Moreover, study findings indicated that all formulation containing OLP extract exhibited better anti-microbial efficiency towards Gram-positive Staphylococcus aureus as compared to Gram-negative Pseudomonas aeruginosa 40,47) . To the best of our knowledge, and the previous report showed that the major constituents for antimicrobial activity present in the olive extract are Cyclotrisiloxane hexamethyl (36.98%) , Cyclotetrasiloxane octamethyl (15.18%) , and Cyclopentasiloxane decamethyl (14.59%) 2) .…”
Section: Anti-microbial Studymentioning
confidence: 95%
“…The antimicrobial study of OLP-loaded SLNs (optimized batch F9) was conducted by utilizing the agar well diffusion method. Bacterial strains like Staphylococcus aureus (Gram s positive) and Pseudomonas aeruginoza (Gram s negative) were used for the evaluation 40) . Nutrient agar plates were prepared under sterile conditions and bacterial suspension (100 µL, concentration around 10 6 CFU/mL) of each bacterium was placed individually on each sterile nutrient agar plate with the help of sterile swabs incubated at 37±0.5℃ for 1 h. Four wells around 8 mm diameters each were produced on each plate with the help of a sterile cork borer.…”
Section: Anti-microbial Studymentioning
confidence: 99%